Effectiveness of BPJS Kesehatan Service Quality Transformation Implementation - Prasetyo, Rizky Fajar; Nurcahyo, Chandra; Wibhawa, Harie; Kumalasari, Anggraeny; Gadistina, Welly; Nugraha, Mohammad Satria; Arma, Sylvia; Gani, Muhammad Yusuf Syahputra (BPJS Kesehatan, 2025)
BPJS Kesehatan has implemented Service Quality Transformation to enhance service accessibility, speed, and equity for National Health Insurance (JKN) participants. This transformation represents a collaborative effort between BPJS Kesehatan and the broader JKN ecosystem, including the Ministry of Health, Health Professional Associations, and Central and Regional Governments, primarily focusing on JKN participant satisfaction. This research aimed to evaluate the effectiveness level of service quality transformation implementation conducted by BPJS Kesehatan. The study employed quantitative methodology. The research used a population of 10.198 BPJS Kesehatan employees, 244 billion JKN participants, and 7.562 stakeholders (Central and Regional Governments, Professional Associations, and Healthcare Facilities). The analysis of service quality transformation implementation effectiveness encompassed two principal indicators: process indicators and impact/outcome indicators. Survey results indicated that the Service Quality Transformation Process Index achieved 87.40%, while the Service Quality Transformation Impact Index on customer perception reached 90.88%. Additionally, the impact of transformation implementation (TML) on Service Performance was measured at 1.94. This research generated recommendations for continuous improvement in service quality implementation, emphasizing the necessity for ongoing training and enhanced collaboration with stakeholders. These findings are expected to contribute significantly to developing health service policies and practices in Indonesia.